Produção e beneficiamento de sementes de soja na Coamo-Unidade de Santo Antônio, Mangueirinha-PR - Magnani, Sandro (2009)
The objective of the present study was to analyze the efficiency of soybean seed production and conditioning at the COAMO, unit of the Santo Antonio, city of Mangueirinha Paraná state, Brazil during a period of five years (2003/2004 to 2007/2008). The efficiency of the company was detached in all phases of the process of soybean seed production. The historical series and referring information to the enrolled area was analyzed according to: approved area, forecast of receiving, act of receiving, improvement of received seeds, seeds analyzed by the laboratory, the percentage of seeds refused in function of the reprobation factors: germination, physical purity and varietal purity, seeds approved as five intervals of germination percentage, the percentage of participation by group of maturation, and the percentage of participation of the obtainors companies. The results show high efficiency in the percentage of approval of the enrolled area, with average of 97,9 % of approval in the period. The efficiency of the receiving act in percentage resulted in an average of 100,4%; the improvement of conditioning in the period was 75,9%; in relation to seeds analyzed by the laboratory the approval index was of 90,5%; the percentage of seeds disapproved in function of the reprobation factors pointed out that 7.1% of the seed produced and analyzed by the laboratory are disapproved by germination and 2.4% are for varietal purity; in relation to germination 33.6% of the produced seed were approved with percentage of germination above 90%, 37.8% were between 89 and 85% of germination, only 21.5% were between 84 and 80% of germination and below 80% of germination were 7.1%, which compose the reprobation factors. It was observed an increase for materials of precocious cycle in the studied period, In relation to the percentage of participation of the obtainors companies, there was a reduction of participation of companies Coodetec and Embrapa and an increase of the Syngenta and appearance of others in the scene.